STRATEGI PENGEMBANGAN USAHA PETERNAKAN KAMBING PERANAKAN ETAWA (Capra aegagrushicus) DI DESA SUKA KECAMATAN TIGAPANAH KABUPATEN KARO - Juneidi Ginting; Posman Marpaung; Kiki P S Munthe (JURNAL REGIONOMIC, 2020)
This study is conducted to determine how the development of breeding of etawa goat goes from breeding plants and marketing products of etawa goat. To know internal and external startegies and swot analyses to support the development of etawa goat in Suka village Tigapanah subdisctrict Karo regency.Convinience sampling control of research areas. The sample is a farmer, a farm group, a chief of the service who endear the farm service, a merchant. Data retrieval through interview, documentation and observation questionnaire.The result of the research obtained were Stregths : (possessed, land of green fodder, bred seeds, and herdsmen of goat) Weakness : (traditional maintenance system, low dairy products and less intensive breeding ) Opportunities : (waste of goat waste can be treated as compost fertilizer, a wide open goat market, the high prices of goats’s milk and high mutton price) Threats : (anger is hard to get green food, competition, goat’s natural ability to stress the weather and feed).